Android-Based Geographic Information System of the Minangkabau Culture and Tourism - Harison, Harison; Husna, Nurul (-)
West Sumatera (Minangkabau) is a tourism destination that has uniqueness in culture and tourism sector. However, culture and tourism information is stiil limited on printed media such as brochure, pamphlet, poster, newspaper, banner, or billboard and from radio and website. To help the tourists who visit West Sumatera, an information medium is needed for easy to access. Geographic Information System can be implemented for various purpose and one of them is tourism. By using Android Smartphone, Geographic Information System for culture and tourism can be designed and developed as an information system which is mobile interactive. This system is using Location Based System (LBS) technology which is developed by using java script. The system can show the location of culture and tourism on the map available on the Android Smarthphone. It can also show information related to hotels and culinary. In this research, an analysis of implementation of geographic information system was done by using questionnaire and it was found that the respondents were satisfied with the system since more than 50% the respondents stated that they strongly agreed and agreed in each statements was 80% of the respondents were satisfied with the minangkabau culture and tourism application with geographic information system.